A tetranuclear cobalt(ii) phosphate possessing a D4R core: an efficient water oxidation catalyst. Issue 15 (27th March 2020) - Dey, Atanu; Kumar, Vierandra; Pal, Shubhadeep; Guha, Anku; Bawari, Sumit; Narayanan, Tharangattu N.; Chandrasekhar, Vadapalli
Abstract : A tetranuclear Co II -phosphate has been found to be an efficient water oxidation catalyst. Abstract : The reaction of Co(OAc)2 ·4H2 O with a sterically hindered phosphate ester, LH2, afforded a tetranuclear complex, [Co II (L)(CH3 CN)]4 ·5CH3 CN (1 ) [LH2 = 2, 6-(diphenylmethyl)-4-isopropyl-phenyl phosphate]. The molecular structure of 1 reveals that it is a tetranuclear assembly where the Co(ii ) centers are present in the alternate corners of a cube. The four Co(ii ) centers are held together by four di-anionic [L] 2− ligands. The fourth coordination site on Co(ii ) is taken by an acetonitrile ligand. Changing the Co(ii ) precursor from Co(OAc)2 ·4H2 O to Co(NO3 )2 ·6H2 O afforded a mononuclear complex [Co II (LH)2 (CH3 CN)2 (MeOH)2 ](MeOH)2 (2 ). In 2, the Co(ii ) centre is surrounded by two monoanionic [LH] − ligands and a pair of methanol and acetonitrile solvents in a six-coordinate arrangement. 1 has been found to be an efficient catalyst for electrochemical water oxidation under highly basic conditions while the mononuclear analogue, 2, does not respond to electrochemical water oxidation. The tetranuclear catalyst has excellent electrochemical stability and longevity, as established by chronoamperometry and >1000 cycle durability tests under highly alkaline conditions. Excellent current densities of 1 and 10 mA cm −2 were achieved with overpotentials of 354 and 452 mV respectively. The turnover frequency of this catalyst was calculated to be 5.23 s −1 with an excellent faradaic efficiency of 97%, indicating the selective oxygen evolution reaction (OER) occurring with the aid of this catalyst. A mechanistic insight into the higher activity of complex 1 towards the OER compared to that of complex 2 is also provided using density functional theory based calculations.